Relationship between microvessel count and post-hepatectomy survival in patients with hepatocellular carcinoma - Nanashima, Atsushi (The WJG Press and Baishideng, 2008)
AIM: To elucidate the relationship between the microvessel count (MVC) by CD34 analyzed by immunohistochemical method and prognosis in hepatocellular carcinoma (HCC) patients who underwent hepatectomy based on our preliminary study. METHODS: We examined relationships between MVC and clinicopathological factors in 128 HCC patients. The modified Japan Integrated Staging score (mJIS) was applied to examine subsets of HCC patients. RESULTS: Median MVC was 178/mm(2), which was used as a cut-off value. MVC was not significantly associated with any clinicopathologic factors or postoperative recurrent rate. Lower MVC was associated with poor disease-free and overall survivals by univariate analysis (P = 0.039 and P = 0.087, respectively) and lower MVC represented an independent poor prognostic factor in disease-free survival by Cox’s multivariate analysis (risk ratio, 1.64; P = 0.024), in addition to tumor size, vascular invasion, macroscopic finding and hepatic dysfunction. Significant differences in disease-free and overall survivals by MVC were observed in HCC patients with mJIS 2 (P = 0.046 and P = 0.0014, respectively), but not in those with other scores. CONCLUSION: Tumor MVC appears to offer a useful prognostic marker of HCC patient survival, particularly in HCC patients with mJIS 2.